Evaluation of risk determination level of players of the Turkish handball super league in the light of demographic variables - Karataş, Özgür; Gündo?du, Cemal; Hacicafero?lu, Serkan (My University, 2013)
This research was carried out to determine the views of the players of the Turkish Handball Super League clubs with some of the demographic variables regarding the risks they perceived. In the study was used the "general screening model" which is one of the descriptive screening methods. The study population was consisted of 435 athletes who were actively engaged in the Turkish Handball Super League teams, and its sample was consisted of randomly and casually selected 376 sporterswho were playing in different clubs. The Gök's questionnaire(2006)of a risk assessment in the sport was used in the study as a data collecting means. The reliability and validity study of the questionnaire used in this research was carried out and the Cronbach's alpha value of the questionnaire used, was found to be 0.71. Arithmetic mean(X), Kruskal-Wallis and LSD, Mann-Whitney U, F tests were used in the data analysis, and the data were analyzed using a statistical software package. The significance level was accepted as 05 in order to determine whether there is a difference among the demographic variables in the conducted survey. The difference among the levels of risk of the athletes participating in the study according to the variables of gender, the year of playing handball and the team played in, was statistically found significant (p> 0.05). In any case, the difference between them in accordance with the variables of age, marital status and education level was not found significant (p>0,05). As the result of research it was found that the female players compared to male players, the players with high school level education compared to the players with university and post-graduate education, the players who are between the ages of 16-17 compared to the players of 18-21, 22-25, 26-29, and over 30 years of age, the players who have been playing handball for 1 to 5 years compared to the players who have been playing handball for 6-10, 11- 15, 16-20, 21 years and above, perceived the risks in a higher level. And it was concluded that the variable of marital status was not a factor in determining the riskfrom the point of the players.
Keywords: Handball; Risk; Risk identification